Canal differentiation in multiporate conceptacles of Mesophyllaceae (Corallinales, Rhodophyta), with recognition of Thallis gen. nov. from South Africa, and Perithallis gen. nov., Printziana gen. nov. and Sunesonia gen. nov. from southern Australia-New Zealand-Chatham. Issue 9 (26th November 2021) - Athanasiadis, Athanasios
ABSTRACT: The structure of canals in multiporate conceptacles of Mesophyllaceae is analysed and several distinct types are recognized. In what appears to be the plesiomorphic condition, canals are straight and bordered by non-differentiated pore cells. In the majority of Mesophyllaceae, pore cells are thinner-wider, starting from basal cells and extending towards the apical opening. This can be coupled with development of triangular (conical) or pyriform canals. Other modifications occur at species or genus level, or across several genera, the most distinctive being formation of cell bars ( Phragmope discrepans ), elongate basal cells ( Melyvonnea ), or branched pore filaments composed of fewer cells than adjacent roof filaments and provided with elongate subbasal (or basal and subbasal) cells ( Thallis-Perithallis, respectively Printziana-Sunesonia ). In Thallis-Perithallis-Sunesonia-Melyvonnea, pore filaments are composed of fewer cells than adjacent roof filaments and terminate below the roof surface. It is postulated that the elongate basal cells in Melyvonnea resulted after loss of basally branched pore cells, an evolutionary step that finds justification in the new genus Sunesonia where homologous cells become reduced or deteriorated. A new thallus organization (aniso-bilateral) characterized by a diminutive ventral perithallium distinguishes Perithallis . Nine new taxa are described, including accounts of their historical record, typifications, comparison of their types to new collections, and the published molecular work that provides further support: Thallis capensis gen. & sp. nov., Perithallis incisa gen. et comb. nov., P. chathamensis (Foslie) nov. comb., Printziana australis gen. & nom. nov. and Sunesonia pseuderubescens gen. et sp. nov.